Description of latrine sanitation conditions and pollution risk factors in Fatukona Village, Takari District, Kupang Regency - Srihayu Takib, Efi; A.R Salmun, Johny; Sahdan, Mustakim (Environmental and Toxicology Management, 2023)
Conclusion Cubluk latrines 115 KK, plengsengan 5 KK, and gooseneck 30 KK don’t meet health requirements. The conditions in Fatukona Village are all related to one main problem that until now has not been resolved, namely the problem of rural sanitation. The formulation of the problem in this study is How to Describe the Sanitary Conditions of Latrines and Risk Factors for Pollution in Fatukona Village,Takari District. The purpose of the study was to determine the sanitary condition of latrines and pollution risk factors in Fatukona Village, Takari District. The research method used is simple random sampling. The results showed that the condition of the latrine building in the cubluk latrine 84 KK plengsengan 1 KK did not meet the health requirements. The sanitary condition of the cubluk latrine floor is 115 households, 5 families and 25 families of gooseneck latrines don’t meet health requirements. The availability of infrastructure facilities in latrines at 115 families’ cubluk latrines, 4 families of plengsengan, and 29 families of gooseneck latrines don’t meet health requirements. Sanitation of fecal drain holes in cubluk latrines 107 families plengsengan 4 families don’t meet health requirements. Risk factors for high pollution in cubluk latrines 64 households, plengsengan 5 families, and Gooseneck 11 families. Conclusion Cubluk latrines 115 KK, plengsengan 5 KK, and gooseneck 30 KK do not meet health requirements.